Cultural Awareness and Translation Teaching at Higher Vocational College: Problems and Solutions - He, Xuelian (Journal of language teaching and research, 2012)
[...]of this feature of language, culture and language are tightly linked and inseparable. "' And declared as firmly as Sapir or Whorf that .No language can exist unless it is steeped in the context of culture; and no culture can exist which does not have at its center, the structure of the natural language.. According to Jeremy Munday (2001), "The term translation itself has several meanings: it can refer to the general subject field, the product (the text has been translated) or the process (the act of producing the translation, otherwise known as translating). In this aspect, translation is a process of exchanging information from one language to another. [...]it is not strange that, nowadays, most people regard translation as a bilingual art of cross-cultural communication, for as we talked in 2.2 that language and culture are intimately bounded and depend on each other. Language itself is a part of culture which Nida calls lingual culture and language, as the most important symbolic system in culture, contains all kinds of cultural deposits in grammar, forms of address as well as texts. [...]translation teachers need to remind students of grammatical differences in the two languages as well as to impart translation skills and instruct knowledge with culture specifics, for those grammatical phenomena also have target cultural characteristics. c. Example Comparison Method: In instruction, teachers can choose some examples of translations both in English and in Chinese with distinct cultural background or characteristics and ask the students to compare those translation versions to find out the best translated ones.